Workers with elderly dependants: employment law's response to the latest care‐giving conundrum. (20th February 2015) - James, Grace; Spruce, Emma
<x xml:space="preserve">Abstract</x> This paper considers how employment laws are being used in response to what we have termed 'the eldercare–workplace conundrum'. It is well known that people are now living longer but health is still failing in a significant percentage of older people, meaning that many adults require care for longer, albeit to varying degrees and for varying amounts of time. Many of these individuals will receive care from relatives or close friends who are participating in the labour market: this is increasingly likely as adults are expected or want to remain in paid work for longer, often into their sixties and seventies. The requirements of elderly dependants can cause these workers huge difficulties and dilemmas as they attempt, across time, to accommodate the particular needs of the person for whom they wish to provide care, often a loved one, and meet the particular demands of their employment relationship. In this paper, we consider why this is an area of social policy that warrants effective legal engagement and consider, drawing on various examples of legal responses in other countries that face similar conundrums, what might improve legal engagement in this area.